Diseño e implementación de un sistema para el monitoreo, supervisión y control de los principales portadores energéticos del Hospital del IESS, Loja mediante el Scada Intouch. - Castillo Suquilanda, José Guillermo (2008)
The technology upgrade today in industries is needed for a better use of these. Health centers located in the tertiary sector, are in the need to continually actualizase therefore one of the measures that worldwide has gained interest is the use of techniques of process automation, such as we find in this Hospital this to provide better service to users; monitoring, supervising, controlling the acquisition of data from a computer. This document describes the three levels designed to reach automation of technological processes highlighted in the IESS Hospital. It has been considered in this project that the implementation of a SCADA system will serve the data acquisition variables of the largest energy carriers. With these classic architecture that can be 4 to 20mA or 0 to 10V, the heterogeneous type as used equipment, sensors, controllers, communication networks and SCADA software from different manufacturers is created. This system shall remain open for future analysis of the variables you wish to incorporate. Found a variety of equipment described in this work, to have a better understanding a simulation of the largest energy carriers is exposed using the InTouch software also plans to meet the approach of the proposed architecture (Annex 7) helping a better understanding of the subject.